Perencanaan Dan Perancangan Galeri Seni Budaya Ende Lio Dengan Pendekatan Arsitektur Neo Vernakuler - Mbuu, Alfons (TEKNOSIAR, 2020)
This research, with a planning location precisely in Kotaraja Village, North Ende District, Ende Regency,aims to create a place for performances, exhibitions, storage and preservation of typical Ende Lio culturalobjects as well as a place for educational information and tourist attractions for the people of Ende Regencyand the community. other areas. The design carried out for the Ende Lio cultural arts gallery uses a neovernacular architectural approach. This is so that it can answer the need for real expression of Ende Liocultural traditions in modern development. The results of this design are expected to be a means and facilityto follow the progress of arts and culture in a more focused manner so that you can enjoy the atmosphere ofdifferent performances and performances regarding arts, as a place for enjoyable recreation and increaseemployment opportunities.